Concurrent inspiratory muscle and cardiovascular training differentially improves both perceptions of effort and 5000 m running performance compared with cardiovascular training alone. Issue 10 (28th February 2008) - Edwards, A M; Wells, C; Butterly, R
Abstract : Objective: To examine whether inspiratory muscle training (IMT) is a useful additional technique with which to augment cardiovascular exercise training adaptations. Methods: 16 healthy untrained males agreed to participate in the study and were randomly assigned to training (TRA; n = 8) and placebo (PLA; n = 8) groups. Pre- and post-training measurements of spirometry and maximal inspiratory mouth pressure (MIP) were taken in addition to i) maximal aerobic power (VO2max ) and ii) 5000 m run time-trial. All subjects completed the same 4 week cardiovascular training programme which consisted of three running sessions (CV1: 5×1000 m, CV2: 3×1600 m, SP1: 20 min run) in each of the 4 weeks. IMT was performed daily by both groups using an inspiratory muscle trainer (POWERbreathe). TRA completed 30 maximal inspirations while PLA inspired 30 times against a negligible resistance. Results: Mean MIP increased significantly in both groups (TRA: 14.5 (SD 6.8)% change, PLA: 7.8 (7.4)% change) from pre- to post-training (p<0.01) but was not significantly related to changes in running performance. Mean CV1 training-repetition runs improved similarly in both groups, but RPE evaluations were significantly reduced in TRA (15.7 (0.7)) compared with PLA (16.6 (0.8)) at week 4 (p<0.05). Pre- to post-training changes in VO2max were well-matched between both TRA (+2.1 (2.3)%) and PLA (+1.3 (2.4)%) while post-intervention 5000 m performance was significantly augmented in TRA compared with PLA (TRA: 4.3 (1.6)%, PLA: 2.2 (1.9)%, p<0.05). Conclusions: The addition of IMT to a cardiovascular training programme augments 5000 m running performance but exerts no additional influence over VO2max compared with a cardiovascular-training group. This is probably due to IMT-induced reduction in perceived effort at high ventilatory rates, which is of greater consequence to longer duration time-trial performances than incremental tests of VO2max .